Risk Factors of Silicosis Progression: A Retrospective Cohort Study in China - Quan, Hua; Wu, Wenhong; Yang, Guanghong; Wu, Yunlin; Yang, Wenlan; Min, Chunyan; Shi, Jinyun; Qin, Lianhua; Huang, Jin; Wang, Jie; Huang, Xiaochen; Mao, Ling; et al. (Frontiers in Medicine, 2022)
Background: Silicosis poses a threat to workers' health due to the irreversible lung lesions. Design: A Retrospective Cohort Study. Methods: A total of 259 patients (80 worked with artificial stone (AS), 179 with non-artificial stone (non-AS)) with confirmed silicosis were included in this study. Forty-one of AS and 91 of non-AS had approximately two years’ follow-up records (lung function tests and high-resolution computer tomography (HRCT)). Compared with the first records, increased, densified, or newly emerging lesions in lung HRCT images were judged as progression of the disease. Cox proportional hazards models were used to determine the risk factors. Kaplan-Meier survival curve and log-rank test were used to compare prognostic factors for cumulative risk of progression. Results: In 132 patients with median follow-up of 24.0 months (IQR, 13.8, 24.9), 66 patients showed progression, in them, 36 (87.8%) were from AS group and 30 (32.9%) from non-AS group. Working experience of AS processing (hazard ratio, 5.64; 95% CI, 2.42-13.14) and complicated silicosis in CT images (26.6% (8/30) in AS, 0% in non-AS) were the main risk factors associated with progression. Forced vital capacity decreased after 1-year (241.5 mL vs 55.2 mL) and 2-year (328.1 mL vs 68.8 mL) follow-up in the two groups (AS vs non-AS). History of anti-tuberculosis medication, chest oppression and pain, ground-glass opacity, pleural abnormalities, and restrictive pulmonary dysfunction were more frequently found on HRCT images in the AS group than non-AS group. Lung functions (DLCO, %) were lower in the current /former smokers than the non-smokers (P < 0.05) in AS patients. Conclusion: Prevention and protection rules are needed to be enforced in the occupation involving AS processing; smoking may be associated with declined lung function in AS patients.